Comparative studies and analysis of efficiency code-based hybrid cryptosystem - Kuznetsov А.А.; Gorbenko Y.І.; Kiian, A.S.; Uvarova А.А.; Kuznetsova, T.Y. (Radiotekhnika, 2018)
The basic principles of construction and operation of McEliece and Niederreiter cryptosystems based on the use of error-correcting codes are considered. A new hybrid cryptosystem, that combines rules of encryption according to the above-mentioned schemes, is proposed. Also, an analysis and comparative studies are carried out in terms of stability, volume of public and private keys, length of ciphertext and relative speed of information transmission of the new proposed scheme and McEliece and Niederreiter cryptosystems presented both in an analytical form and by means of a graphic. Comparative studies revealed that the hybrid cryptosystem retains the positive aspects of its predecessors, as well as allows increase in the relative transmission rate with the preservation of the stability indicator to the classical and quantum cryptanalysis, but, unfortunately, one important limitation is still preserved - a large size of the required key data.